2019
DOI: 10.1186/s12970-019-0316-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a caffeine-like supplement, TeaCrine®, on muscular strength, endurance and power performance in resistance-trained men

Abstract: BackgroundTeaCrine® is the synthetic version to naturally occurring theacrine (1, 3, 7, 9-tetramethyluric acid) found in the leaves of Camellia kucha tea plants. A few studies have examined the effects of TeaCrine® on cognitive perception, but no research exists examining its effects on resistance exercise performance. The purpose of this study was to determine the efficacy of TeaCrine®, a caffeine-like compound, on maximal muscular strength, endurance, and power performance in resistance-trained men.MethodsTw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 43 publications
2
25
0
8
Order By: Relevance
“…However, our data do not support this hypothesis as we found no significant acute or chronic effects of DYM alone or in combination with TCR on systolic or diastolic blood pressure. Rather, our findings appear to corroborate those of four other studies examining TCR in humans [14,15,17,19], and one in rats [34], which reported no observable negative effects on blood pressure [14,17], even when TCR was combined with caffeine [15,19].…”
Section: Cardiovascular Functionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, our data do not support this hypothesis as we found no significant acute or chronic effects of DYM alone or in combination with TCR on systolic or diastolic blood pressure. Rather, our findings appear to corroborate those of four other studies examining TCR in humans [14,15,17,19], and one in rats [34], which reported no observable negative effects on blood pressure [14,17], even when TCR was combined with caffeine [15,19].…”
Section: Cardiovascular Functionsupporting
confidence: 90%
“…Due to purported synthesis from caffeine in some plants and structural similarities to caffeine [5,11], both theacrine and methylliberine are theorized to produce similar physiological effects with less side effects, potentially due to their different affinities with adenosine receptors [11,12]. Although theacrine was first discovered in 1937 [13], little research (to our knowledge, only seven studies) was conducted on theacrine's effects on human health and performance until recently [14][15][16][17][18][19][20]. Previous cell and animal model investigations on theacrine reported improved antioxidant capacity [20] and anti-inflammatory responses [21], as well as analgesic [21], antidepressive [22], and sedative/hypnotic [23] mood states.…”
Section: Introductionmentioning
confidence: 99%
“…From a methodological point of view the number of participants in the present study was relatively small but in the range of similar studies employing a randomized cross-over design (Cesareo et al 2019;Gillen et al 2019;Fryer et al 2019). Therefore, more subjects would have given more statistical power for the data interpretation, however the small sample size allowed us to monitor and control each training session and off-training activity.…”
Section: Limitationsmentioning
confidence: 97%
“…Theacrine is a purine alkaloid that structurally similar to caffeine, and various studies have examined its e cacy as a neuroactive ingredient (10)(11)(12). Aside from potential neurotrophic effects, there are limited data in rodents suggesting theacrine-based supplements can reduce in ammation (13,14), modulate mitochondrial function (15), and activate sirtuins (15).…”
Section: Introductionmentioning
confidence: 99%